Visszaemlékezés Szénássy Barnára - Győry, Kálmán (Gerundium, 2014)
REMEMBERING BARNA SZÉNÁSSY. In relation to the previous essay, the eulogy, presented at the 100th anniversary of the birthday of Barna Szénássy at the University of Debrecen, is published here. he author remembers the outstanding igure of the historical research of mathematics through personal stories of a student, a colleague, and a good friend.